Spatiotemporal analysis of air pollutants and forest vegetation characteristics in Gangwon Province, South Korea - Lee, Ui-Jae; Kim, Dan-Bi; Lee, Do-Won; Kim, Myeong-Ju; Lee, Sang-Deok (Frontiers in Forests and Global Change, 2025)
Understanding the interactions between air pollutants and vegetation is essential for developing effective air quality management strategies, particularly in forest-rich regions. This study investigates the spatial and temporal characteristics of air pollution in Gangwon Province, South Korea, from 2019 to 2023, focusing on pollutant concentrations, emissions, and their relationships with vegetation. We utilized data from the national air quality monitoring network, including PM10, PM2.5, and O3 concentrations, along with emissions data from the Clean Air Policy Support System (2019–2021) and NDVI data derived from MODIS satellite observations. Our analysis revealed that PM concentrations were highest in inland cities such as Chuncheon, Hongcheon, and Wonju, largely due to atmospheric stagnation and topographical confinement, while coastal areas exhibited lower levels owing to maritime dispersion. O? levels were elevated in coastal and mountainous regions, influenced by land-sea breeze circulation. Emissions varied regionally, with traffic and fugitive dust dominating in urban inland areas, biomass burning in Gangneung, and industrial emissions in Donghae. Seasonal patterns showed PM peaking in spring and winter, while O3 peaked in summer. NDVI exhibited a consistent negative correlation with PM, particularly PM2.5, indicating the potential mitigating effect of vegetation. In contrast, O3-NDVI correlations varied regionally, showing positive associations in some western areas. These findings emphasize the importance of region-specific air quality policies, including green space expansion for PM control and precursor emission management for O3, along with continued monitoring of external pollutant inflows and meteorological stagnation.